Fast Sampling Control of Singularly Perturbed Systems with Actuator Saturation and L2 Disturbance. (16th September 2015) - Miao, Yanzi; Ma, Lei; Ma, Xiaoping; Zhou, Linna
Abstract : We will consider the problem of fast sampling control for singularly perturbed systems subject to actuator saturation andL 2 disturbance. A sufficient condition for the existence of a state feedback controller is proposed. Under this controller, the boundedness of the trajectories in the presence ofL 2 disturbances is guaranteed for any singular perturbation parameter less than or equal to a predefined upper bound. To improve the capacity of disturbance tolerance and disturbance rejection, two convex optimization problems are formulated. Finally, a numerical example is presented to demonstrate the effectiveness of the main results of this paper.